Impact of human activities and vegetation changes on the tetraether sources in Lake St Front (Massif Central, France). (September 2019) - Martin, Céline; Ménot, Guillemette; Thouveny, Nicolas; Davtian, Nina; Andrieu-Ponel, Valérie; Reille, Maurice; Bard, Edouard
Highlights: Downcore brGDGTs in Lake St Front sediments have a mixed origin. ΣIIIa/ΣIIa ratio in the past can be used to reveal brGDGT source changes. A gradual shift in brGDGT sources occurred during the Holocene in Lake St Front. Shift in brGDGT sources results from changes in erosive dynamics of the catchment. brGDGT distribution is impacted by vegetation changes and human activities. Abstract: The distribution of branched glycerol dialkyl glycerol tetraethers (brGDGTs) has been shown to correlate with mean annual air temperature and is increasingly used for paleoclimate reconstructions, in particular in lakes. Numerous studies have reported in situ production of brGDGTs in lakes. These brGDGTs have different distributions compared with those produced in soils and their mixing hampers paleoclimate reconstructions. Very few tools exist to determine brGDGT sources in the present and to trace their changes in the past linked with environmental changes of climatic or anthropogenic origin. While human activities are known to affect both soil and aquatic ecosystems, particularly bacterial communities, the specific impacts on brGDGT distributions are poorly investigated. High resolution analyses of brGDGTs were carried out on Holocene sediments and catchment soils of Lake St Front (Massif Central, France) in association with sedimentological, palynological, and geochemical analyses. Comparison of brGDGT distributions in sediments and soils revealed their mixed origin. For the first time, we tested the reliability of the ΣIIIa/ΣIIa ratio in lakes which indicated a gradual shift from aquatic to terrigenous brGDGT sources over the Holocene. This shift was supported by sedimentological and geochemical indices. Three events with a high proportion of terrigenous brGDGTs (6–5.5, 2.8–2.5, and 2–0.2 kyr cal BP) coincide with changes in vegetation in the catchment area, driven by climate and/or human activities. This suggests that vegetation modifications in the watershed impact brGDGT distributions and may thus bias brGDGT-based paleoclimatic reconstructions.